Asymmetrically lesioned mesencephalon in healthy rodents: call for caution - Pioli, Elsa Y.; Dovero, Sandra; Bioulac, Bernard H.; Gross, Christian E.; Bezard, Erwan (Brain research, 2004)
Stereological counting of tyrosine-hydroxylase immunoreactive (TH-IR) neurons in the mesencephalon is a pivotal parameter in assessing the extent of lesioning in animal models of Parkinson's disease. We here show that the number of TH-IR neurons often appears abnormally decreased in healthy—commercially available—mice and rats, although both the number of Nissl-stained cells and the striatal dopaminergic innervation are unaffected. This potential bias in assessing extent of neurotoxin-induced lesion and subsequent protection by pharmacological manipulation prompts us to call for caution in setting up experimental designs.